The Importance of Jiangsu's Economy in the Formation of Regional Pattern of the Emerging Chinese Market - TAN, Teck Meng (Institutional Knowledge at Singapore Management University, 1997)
This paper analyses the characteristics of market development in Jiangsu province and explains how the development of market-oriented TVEs has moved Jiangsu’s economy towards a dynamic market economy. It argues that the leading development of market mechanism in Jiangsu has enabled Jiangsu’s economy to become one of the most important regional market centers in China.